Ethambutol and isoniazid induced severe neurotoxicity in a patient undergoing continuous ambulatory peritoneal dialysis. (18th May 2018) - Si, Meijun; Li, Huiqun; Chen, Yanru; Peng, Hui
Abstract : Ethambutol (EMB) and isoniazid (INH) are the first-line antituberculosis (anti-TB) drugs. However, their neurotoxicity could cause adverse effect and the patients with end-stage renal disease are especially vulnerable due to the reduction in renal drug clearance. Here, we report a 36-year-old man receiving peritoneal dialysis developed progressive paralysis in lower extremities, vision loss and hoarseness 4 months after anti-TB treatment with INH, EMB and rifapentine because of concomitant pulmonary tuberculosis. A diagnosis of EMB/INH-induced peripheral neuropathy, retrobulbar neuritis and laryngoparalysis was made. The patient's neuropathy gradually improved 2 years after discontinuation of EMB/INH. Since EMB and INH may cause simultaneously severe and complex multineuropathy in dialysis patients, their adverse effects should be closely supervised in dialysis patients.